Management of a Residual VSD 60 Years after One of the First Operations Worldwide - Hegazy, Yasser Yehia; Koriem, Mohamed; Keshk-Hegazy, Noha Samir; Sodian, Ralf (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Background Although surgical closure of ventricular septal defect (VSD) is the gold standard treatment, patients are subjected to deterioration in the following decades. We will present here the first case in literature surviving 60 years after surgical VSD closure with a residual VSD and presenting again for surgery.Case Description A 68-year-old male patient who underwent surgical closure of a perimembranous VSD in Berlin in 1959. Postoperatively, a small residual VSD was noticed, which was well tolerated over six decades. He presented 60 years postoperatively with severe aortic regurgitation, tricuspid regurgitation, and moderate mitral regurgitation.
Keywords: history; congenital heart diseases; CHD; cardiovascular surgery